Management of mucous membrane pemphigoid in a joint oral medicine–dermatology clinic. (1st August 2020) - Finn, D. J.; Graham, C.; Holt, D. J.; Kelly, R.; Rajlawat, B. P.; Yesudian, P. D.
Summary: Background: Mucous membrane pemphigoid (MMP) comprises a group of immunobullous diseases involving the mucosa and skin. Potential sequelae include painful mucosal erosions, vision loss and laryngeal stenosis. Aim: To characterize the features of patients with MMP seen within an Oral Medicine setting, including clinical features, immunofluorescence results and response to treatment. Methods: A retrospective case note analysis was undertaken. Treatment effect was divided into response and nonresponse using predetermined adjective terms. Results: In total, 42 cases of MMP were identified (18 men, 24 women), mean age 65 years (range 36–85 years). Oral involvement was most common on the gingivae ( n = 38; 90.5%) while the most common extraoral sites involved were ocular ( n = 13; 31.0%) and skin ( n = 12; 28.6%). Features of MMP were found in 21 of 34 (61.8%) of routine biopsies, 31 of 34 (91.2%) direct immunofluorescence samples and 8 of 25 (32.0%) indirect immunofluorescence samples. Topical corticosteroids provided effective symptom control in 9 of 42 cases (21.4%), while systemic therapy was used in 31 of 42 patients (73.8%). Dapsone was prescribed for 25 patients, of whom 18 (72.0%) responded. Mycophenolate mofetil was used in 13 cases and had a response rate of 46.2%. Overall, 27 of 42 patients (64.3%) achieved a response using a tolerable topical or systemic treatment. Conclusion: This series demonstrates that MMP has a female predominance and is a disease of older age, with a predilection for specific oral sites. Direct immunofluorescence has a high sensitivity in detecting features of MMP. Although some patients achieve adequate symptom control with topical corticosteroids, many require systemic therapy.